Unveiling synergies: the mediating role of China's OFDI and intelligent transformation in advancing green total factor productivity - Chen, Shunru; Alexiou, Constantinos; Xie, Ying (Wiley, 2025)
This research focuses on the impact of intelligent transformation on green total factor productivity (GTFP) within China's manufacturing enterprises from 2010 to 2022. To assess the extent of intelligent transformation across the sector, the study adopts natural language processing and the non‐radial SBM‐ML index to measure GTFP. Utilizing threshold and mediation analysis, we explore how outward foreign direct investment (OFDI) affects intelligent transformation and GTFP while additional robustness tests supplement the analysis. The study also considers the variability in the impact of intelligent transformation at enterprise, industry, and regional levels. The results reveal a significant positive relationship between intelligent transformation and GTFP, notably stronger in non‐OFDI firms and more pronounced in heavily polluting industries. In particular, enterprises with smaller scale of FDI and those in China's middle region see more substantial benefits.
Keywords: Business & Management; 3501 Accounting, auditing and accountability; 3505 Human resources and industrial relations; 3507 Strategy, management and organisational behaviour; China; green total factor productivity; intelligent transformation; manufacturing; outward foreign direct investment